Why states fail & how states recover - Mills, Greg (2015)
Somalia and its twin Somaliland are prototypes of states that fail and states that recover. The difference between Somalia and Somaliland is the difference between a peace owned and a rent-seeking peace. Local ownership is but one aspect of the conditions for state recovery.